The efficacy of supplementary sonic irrigation using the EndoActivator® system determined by removal of a collagen film from an ex vivo model. (13th December 2017) - Bryce, G.; MacBeth, N.; Gulabivala, K.; Ng, Y‐L.
Abstract: Aim: To evaluate the efficacy of sonic irrigation (EndoActivator ® ) using various polymer tips and power settings in a stained collagen ex vivo model. Methodology: The root canals of fifty human, straight single‐rooted extracted teeth were prepared to size 40, .08 taper. The roots were split longitudinally; stained collagen applied to the canal surfaces, photographed and re‐assembled. The canals were subjected to syringe without supplementary (group 1, n = 10) or with supplementary sonic (groups 2–5, n = 10) irrigation. EndoActivator ® tip sizes (size 15, .02 taper for groups 2 and 3; size 35, .04 taper for groups 4 and 5) and power settings (low for groups 2 and 4; high for groups 3 and 5) were tested. After irrigation, the canals were re‐photographed and the area of residual stained collagen was quantified using the UTHSCA Image Tool program (Version 3.0). The data were analysed using Wilcoxon signed rank test and general linear mixed models. Results: Supplementary sonic irrigation using EndoActivator ® resulted in significantly ( P < 0.0001) less residual collagen compared with syringe irrigation only. Agitation of irrigant using the large EndoActivator ® tip with high power resulted in significantly less (22.4% – 29.5%) residual collagen compared to other combinations (large tip/low power P = 0.001; small tip/low power P = 0.01; small tip/high power P = 0.04). There was no significant difference amongst the latter three groups ( P > 0.5). Conclusions: Supplementary sonic irrigation using the EndoActivator ® system was significantly more effective in removing stained collagen from the canal surface than syringe irrigation alone. EndoActivator ® used with large tip (size 35, .04 taper) and high power setting in size 40, .08 taper canals was more effective than other combinations.